MICROPLASTIC IN INDIA A SHODDY AFFAIR - MUKHERJEE, ABHISHEK; BHATTACHARJEE, ARCHISMAN; ROY, AOISHIK (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Small sized fragmented plastic or microplastic contamination is widespread and considered as one of the major problems of aquatic environment. Ability to resist bio-degradation amplifies longevity, long transportation and aggregation, enables microplastics to find their sink in the drinking water. The situation in India is more critical as sources of microplastics are far too many and the high sediment flux in the rivers may easily facilitate the process of fragmentation during typical tropical climate, making the aquatic ecosystem of India extremely vulnerable. Detailed research and careful monitoring activities could bring clearer picture of the scenario and assess the impact of plastics on environment and biota. Some mechanism through which the emissions at the source could be checked or some other ways to reduce and reuse plastic waste or some new novel business solutions are essential to tackle this problem.